Comparison of the effect of patient-controlled epidural anesthesia (PCEA) and parenteral use of opioid analgesics on the postpartum condition of the newborn - Michał Michalczyk; Dorota Torbé; Andrzej Torbé (Kazimierz Wielki University, 2018)
Aim: To evaluate the effect of different forms of pharmacological intrapartum analgesia on the birth state of the newborns by comparing the results of blood gas umbilical cord artery as well as Apgar score at 5th minute of life. Material and methods: 160 pregnant women ≥ 37 weeks, which attempted vaginal delivery in the Department of Obstetrics and Gynecology of the Pomeranian Medical University in Szczecin, were divided into four groups: 1. PCEA (n = 40) women giving birth under patient-controlled epidural anesthesia (PCEA) in a horizontal position; 2. Pethidine (n = 30) women giving birth subjected to analgesia by parenteral supply of pethidine; 3. Fentanyl (n = 30) women giving birth subjected to analgesia by parenteral supply of fentanyl; 4. Control (n = 60) women giving birth without analgesia. In each of the groups newborn status was assessed on the basis of Apgar score in the 5th minute of life and on the basis of umbilical artery cord blood pH immediately after birth. Results: The analysis showed no significant differences in Apgar score in the 5th minute of life between the study groups, as well as between the subgroups of nulliparous and multiparous. Analysis of the blood pH value of the umbilical cord artery revealed that in the case of pethidine anesthesia the values were significantly lower compared to the other groups. While patients anesthetized by PCEA demonstrated statistically significant maximum value of this parameter. Similar relations were observed in the subgroups of nulliparous. No differences were detected in this range between subgroups of multiparous. Conclusions: The use of patient-controlled epidural anesthesia does not affect the postnatal status of newborn's evaluated on the basis of the analysis of umbilical cord artery blood pH and Apgar score at the 5th minute of life. In comparison to the formula of patient-controlled epidural anesthesia, as well as to the parenteral supply fentanyl anesthesia, intrapartum parenteral supply of pethidine results in a significantly lower pH values of umbilical artery cord blood of newborns immediately after birth.